Establishment of a functional and sustainable bio-system engineering process for the saccharification of starch with industrial focus (Jahangirnagar University Journal of Biological Sciences, 2019)
Enzyme immobilization provides an excellent opportunity to use the enzymes for several times with greater productivity. The main aim of the present study is the establishment of a functional and sustainable bio-system engineering process based on immobilized α-amylase enzyme for the saccharification of starch with industrial focus as well as cost effective sustainable bioprocess system by using indigenous industrial waste materials as carrier agents. In this study, α-amylase was immobilized in different types of support matrices like alginate, sawdust, sugarcane bagasse and the activity of immobilized enzymes were analyzed for the breakdown of starch. The experimental results showed that the productivity of immobilized enzyme was around 2.3 times higher than the free enzyme. Conjugates of bagasse-alginate showed the highest result. A fixed batch immobilized enzyme bioreactor had been developed which could be used for the production of various valuable products in the industrial scale.Jahangirnagar University J. Biol. Sci. 8(1): 45-55, 2019 (June)